Electoral dynamics in Malaysia findings from the grassroots (Strategic Information and Research Development Centre, 2014)
"Malaysia's 13th general election, held 5 May 2013, saw an unprecedentedly close race between the incumbent Barisan Nasional (National Front, BN) and Pakatan Rakyat (People⁰́₉s Alliance, Pakatan) coalitions. For the first time in Malaysian history, a challenger coalition not only kept the BN from regaining the two-thirds parliamentary super-majority it had lost in the previous election, in 2008, but eked out a slim majority of the popular vote. While any Malaysian election is a big event, this one in particular merits close scrutiny. The present volume offers evidence and analysis with which to probe both the merits of common interpretations of who voted how, and why, and to suggest new readings of Malaysian electoral politics."--Front cover flap.